Changes in hormones of the somatotropic axis associated with postpartum reproductive infections in Murrah buffaloes (Bubalus bubalis) - Mili, Bhabesh; Pandita, Sujata (Indian Journal of Dairy Science, 2021)
This study was designed to investigate the risk association of hormones of the somatotropic axis with postpartum infections/ disorders in Murrah buffaloes. A total of six (n=6) healthy pregnant Murrah buffaloes and 23 symptomatic buffaloes with symptoms indicative of metritis (n=5), endometritis (n=6) mastitis (n=8), and retention of placenta (ROP) (n=4) were selected from the ICAR-NDRI Cattle herd. Blood samples were collected by jugular venipuncture in sterile heparinized vacutainer tubes from each healthy buffalo at 6.00 A.M. on days -21, -14, -7, 0, +7, +14, +21 relative to calving. Blood samples were also collected from unhealthy buffaloes twice in sterile heparinized vacutainers on alternate days as and when the symptoms of reproductive abnormalities were noticed. The results revealed that the plasma growth hormone was significantly (P<0.05) elevated in buffaloes exhibiting symptoms of metritis (7.40±0.96 ng /ml), mastitis (9.23±1.60 ng /ml), and ROP (6.63±0.80 ng/ml). Similarly, plasma insulin level was significantly higher (P<0.05) in buffaloes infected with endometritis, mastitis, and ROP. But, the plasma IGF-1 registered significantly lower in buffaloes exhibiting symptoms of metritis, endometritis, and mastitis except for ROP (122.21±5.10 ng/ml). From the experiment, it can be inferred that plasma growth hormone, insulin, and IGF-1 were differed significantly in infected buffaloes from the healthy ones and could be used for the risk assessment of postpartum infection in buffaloes.